2020
DOI: 10.1002/htj.22019
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady flow and heat transfer of tangent‐hyperbolic fluid: Legendre wavelet‐based analysis

Abstract: The objective of the current article is to explore the unsteady flow and heat transfer of magnetohydrodynamics tangent‐hyperbolic fluid flow over a stretching sheet. The governing flow model is transformed into a nonlinear set of ordinary differential equations by utilizing the appropriate similarity techniques. A new modification is introduced into the traditional Legendre wavelet method to obtain the results of the model mentioned above. The classic wavelet scheme is unable to find the solution for an infini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Farhan et al 25 investigated the impact of the difference in viscosity and thermal conductivity on a nonisothermal plane sheet with suction blowing. Also, several authors studied different aspects in various fluids and references are found therein 26–37 …”
Section: Introductionmentioning
confidence: 99%
“…Farhan et al 25 investigated the impact of the difference in viscosity and thermal conductivity on a nonisothermal plane sheet with suction blowing. Also, several authors studied different aspects in various fluids and references are found therein 26–37 …”
Section: Introductionmentioning
confidence: 99%
“…A section of fluid dynamics allied to the measurement of an electrically conducting fluid in the appearance of the magnetic field is recognized as magnetohydrodynamics (MHD). [1][2][3][4][5][6][7] In numerous realistic applications that require a strong magnetic field and low electron density, Hall effects cannot be ignored, that is, once the intensity of the magnetic field is strong or fluid density is low, the Hall current occurrence is noteworthy. As electron transport induced electrons to move quicker than ions, as an impact isotropic conductivity is generated, this is familiarly known as Hall current.…”
Section: Introductionmentioning
confidence: 99%
“…Hamid et al 33 considered the Galerkin approach to analyze the MHD flow of nanofluid along converging/diverging channels. Usman et al 34 discussed unsteady flow and heat transfer of a tangent-hyperbolic fluid. Recently, Khan et al, 35 Soomro et al, 36 and Hamid et al 37 discussed Brownian motion and thermophoresis effects on nanofluid flow problems.…”
Section: Introductionmentioning
confidence: 99%